Total gastrectomy: About 45 cases - Carriquiry, Luis A.; Bergalli, Luis E.; Olivera, Daniel; Priario, Julio C.; Pradines, Jorge C. (Cirugía del Uruguay, 1982)
Total gastrectomy has a bad reputation among surgeons which it does not deserve. After their experience with 45 total gastrectomies; 43 of which were performed on gastric cancer extended to the spleen and pancreas and reconstructed by means of an esophago-ieiunostomy with a disfunctionalyzed loop; the authors remark that: 1- Its mortality; yet high - in his series reaches 22% however not different from the main series issued in Europe, the U.S. and Latín America; can be lowered through a well planned Prophylactic scheme of is principal postoperative complications: failure of the esophago-ieiunal anastomosis uture and respiratory and throm oem bolle complications. 2- that lite after the operation is of a much better quality than it was said before, if there is no neoplastic recidivation and especially if the transit is reconstructed in such a way so as to avoid enteroesophageal reflux. A Roux Y loop or any of its functionally similar varins as the HiveWarren loop modified by Estefan and Praderi are recommended.